Enhance Historical Source Analysis with Muara Takus Temple's Local History E-Modules - Asyrul Fikri; Bunari Bunari; Yuliantoro Yuliantoro (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
The purpose of this study is to determine how well high school students' reading comprehension and ability to analyse historical materials are improved by the Muara Takus Temple local history e-module. A quasi-experimental design with a pretest-post-test control group was the study methodology employed. Students from SMA Negeri 1 Bangkinang made up the 56-person sample for the study. The experimental group, which utilized the e-module, and the control group, which did not use the e-module, were the two groups formed from the research sample. Both a pre-test and a post-test were used to gather data. Data analysis using the t-test revealed that, in comparison to the control group, the experimental group significantly improved its capacity for evaluating historical materials (p-value = 0.001 <0.05). Thus, it was determined that the utilization of Candi Muara Takus' local history e-module had a substantial impact on students at SMA Negeri 1 Bangkinang's ability to read and analyse historical texts. The study's conclusion is that the local history e-module has the potential to help students become more proficient readers and analysts of historical materials. This demonstrates the necessity of integrating technology into history instruction to improve students' analytical abilities and get them ready to comprehend history more fully.